A new bisphosphonate derivative, CP, induces gastric cancer cell apoptosis via activation of the ERK1/2 signaling pathway - Wang Hai-jun; Liu Yu; Fan Li-qiao; Han Cai-li; Jiang Ye; Cheng Shu-jie; Li Yong (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of a new derivative of bisphosphonates, [2-(6-aminopurine-9-yl)-1-hydroxy-phosphine acyl ethyl] phosphonic acid (CP), on human gastric cancer. Methods: Human gastric cancer cell lines (SGC-7901, BGC-823, MKN-45, and MKN-28) and human colon carcinoma cell lines (LoVo and HT-29) were tested. Cell growth was determined using the MTT assay. Flow cytometry, Western blot, caspase activity assay and siRNA transfection were used to examine the mechanisms of anticancer action. Female BALB/c nude mice were implanted with SGC-7901 cells. From d6 after inoculation, the animals were injected with CP (200 μg/kg, ip) or vehicle daily for 24 d. Results: CP suppressed the growth of the 6 human cancer cell lines with similar IC50 values (3239 μmol/L). In SGC-7901 cells, CP arrested cell cycle progression at the G2/M phase. The compound activated caspase-9, increased the expression of pro-apoptotic proteins Bax and Bad, decreased the expression of anti-apoptotic protein Bcl-2. Furthermore, the compound selectively activated ERK1/2 without affecting JNK and p38 in SGC-7901 cells. Treatment of SGC-7901 cells with the specific ERK1/2 inhibitor PD98059 or ERK1/2 siRNA hampered CP-mediated apoptosis. In the human gastric cancer xenograft nude mouse model, chronic administration of CP significantly retarded the tumor growth. Conclusion: CP is a broad-spectrum inhibitor of human carcinoma cells in vitro, and it also exerts significant inhibition on gastric cancer cell growth in vivo. CP induces human gastric cancer apoptosis via activation of the ERK1/2 signaling pathway.